CULTURAL DIMENSIONS IN ENGLISH TEXTBOOK - Sanusi Hidayat (English Education Department Slamet Riyadi University Surakarta, 2023)
The aim of this research was to describe the kind of Cultural dimensions that appears inthe English textbook. The research technique applied in this study was a content analysis methodthat took a qualitative approach. Construction of a checklist, analysis of a textbook, coding,categorization, and interpretation were used to obtain the data. Based on Adaskou, Britten, andFahsi (1990) statement, cultural dimensions in the textbook derived into four senses: (1) aestheticsense, (2) sociological sense, (3) semantic sense, and (4) pragmatic sense. Based on the results ofdata analysis of the kind of Cultural dimensions that appears in the textbook, the Bahasa InggrisThink Globally Act Locally textbook for ninth grade in junior high school offered a lot of culturalmaterial. It was evident from the kind of culture dimensions that was presented in textbooks. Thefindings revealed Aesthetic sense dominance with 37%, 27% to the Sociological sense, 21% to theSemantic sense, and just 15% to the Pragmatic sense.Keywords : Analysis, Culture, English textbook, Junior High School